Donor assistance and political reform in Tanzania - Aili Mari Tripp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Tanzania has been a relative success story in Africa in terms of political reform. While foreign aid has helped strengthen institutions that advance accountability, it simultaneously supports a status quo that undermines accountability and democratization. This study first explores the ways in which foreign donors directly strengthen civil society, parties, the media, as well as legislatures and the judiciary. It then looks at the ways in which donor support has unintended consequences in undermining accountability through the provision of general budget support and through support of policies that undercut vertical accountability in decentralization and in public goods provision.
Keywords: D72; F35; N47; 330; Tanzania; democratization; accountability; foreign aid; decentralization; public goods; Politische Reform; Demokratisierung; Entwicklungshilfe; Dezentralisierung; Öffentliche Güter; Tansania